Labor relations law :cases and materials /Theodore J St Antoine, Charles B Craver, Marion G Crain - St. Antoine, Theodore J
This well-organized, comprehensive text covers labor law from organizing efforts through the collective bargaining process, and the economic weapons available to employees, labor organizations, and employers. It explores the statutory limits imposed on picketing, and various forms of secondary activity, and distinguishes between lawful and unlawful forms of union security provisions. It includes: cases pertaining to the judicial enforcement of grievance-arbitration provisions, and explicating the scope of federal preemption of state statutes regulating labor relations; discussion of the decline of private sector labor unions; and the main judicial and Labor Board decisions interpreting the NLRA.